Analysis of socio-family supports and conflicts of women in Spanish prisons - María del Mar García-Vita (Revista de Paz y Conflictos, 2017)
The prison isolates and hinders the creation of an environment in which family and social relationships develop positively. In the personal networks of inmates both processes of social support and conflict with their relatives and close ones are given. In this article are described the characteristics of the women prisoners’ support networks in Spain and how interpersonal conflicts affect on the configuration of those networks. We analyze the results of a research that has had a sample of 599 female participants (538 by survey respondents and 61) in a national study that has covered 42 prisons. The data are quantitative (treated with the SPSS 20 software version) and qualitative (analyzed with interpretation and content analysis techniques). The results lead us to point out that the prison intervention has in consideration the positive inmates interpersonal relationships rather than focusing all their attention those family and social ties that are shown as negative or risky. This bet we do on prison intervention fits perfectly with socio-educational approaches that comply with the guiding principles of peace education.